(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe results of nursing care, health counseling for patients after ureter laser lithotripsy at Vinmec Time City Hospital. Methods: A cross-sectional study on 93 patients after ureter laser lithotripsy at Vinmec Times City from December 2020 to July 2021. Data were collected through checklist about nursing care and health counseling and quesstionnaire about knowledge urinary calculus by observation and interviews. Results: 95.7% of patients received satisfactory nursing care. 100% received full monitoring of general condition, pain control and catheter care. The postoperative complication rate was 11.9%. 100% received health counseling, 82.8% had good knowledge after counseling. Conclusion: The quality of nursing care and health counseling for patients after ureter laser lithotripsy at the hospital achieved high effectiveness.